Corporate governance practices in Portugal - Lisboa, Inês (2021)
Corporate governance is not a new topic but has become more relevant in the last years due to the financial crisis of 2008, when diverse companies went to bankruptcy, and investor’s protection was weakened. Thus, diverse countries have revised corporate governance mechanisms and recommendations to restore the confidence of investors and the transparency of companies’ financial reports. This work aims to explain the evolution of corporate governance practices in Portugal. We provide information on corporate governance’ legal framework. Then we explain ownership structures and board of directors’ and directors’ remuneration practices. Shareholders’ rights and activism are also explained. Finally, we linked the topic of corporate governance and companies’ performance and social responsibility. This work contributes to increasing literature review on corporate governance practices, by presenting the evolution of corporate governance practices in a specific country, Portugal.